9H‐Carbazole Derivatives Containing the N‐Benzyl‐1, 2, 3‐triazole Moiety as New Acetylcholinesterase Inhibitors. Issue 5 (27th March 2015) - Akrami, Hamidreza; Mirjalili, Bibi F.; Khoobi, Mehdi; Moradi, Alireza; Nadri, Hamid; Emami, Saeed; Foroumadi, Alireza; Vosooghi, Mohsen; Shafiee, Abbas
<x xml:space="preserve">Abstract</x> A series of triazole‐containing carbazole derivatives were designed as new anti‐acetylcholinesterase (AChE) agents. The target compounds 6a–q were simply prepared via a one‐pot three‐component click reaction of N‐propargyl‐9H‐carbazole, sodium azide, and an appropriate benzyl halide. The in vitro anti‐cholinesterase assay showed that the unsubstituted benzyl derivative 6p along with the 2‐F, 2‐Me, 3‐Me, 3‐MeO, and 3‐F analogs (6a, 6c, and 6g–i) had significant anti‐AChE activity (IC50s ≤ 3.8 μM). Among them, the 2‐methylbenzyl derivative 6c with an IC50 value of 1.9 μM was the most active compound. The SAR studies revealed that small halogen atoms such as the fluorine atom or electron‐donating groups such as methyl or methoxy at the ortho or meta positions of the benzyl pendent group could be tolerated or improved the anti‐AChE activity.